Optimizing the Role of TWKS Museum as A History-Based Educational Tourism Site in South Sumatra - Tomy Wijaya; Fatimah Alauwiyah; Muhammad Reza Pahlevi; Hudaidah Hudaidah; Alif Bahtiar Pamulaan (MASI Mandiri Edukasi, 2025)
This study examines the use of the Taman Wisata Kerajaan Sriwijaya Museum (TWKS) as a history-oriented educational tourist site in South Sumatra. Notwithstanding its significant cultural and educational potential, TWKS has not been effectively leveraged as a learning resource or historical tourist destination. This study employed a descriptive qualitative methodology, including observations, interviews with 12 participants (museum staff, educators, and visitors), and documentation. The data analysis was conducted using Miles and Huberman's interactive model, which included data reduction, presentation, and verification. The findings identify three primary impediments: constrained digital innovation, insufficient institutional collaboration, and minimal public advocacy, which obstruct TWKS's role as a hub for education and cultural tourism. This museum has the potential to evolve into a vibrant learning environment that links historical knowledge with modern educational experiences. This study advocates for the revitalization of TWKS through digital transformation, enhanced academic partnerships, and the creation of interactive programs. This study enhances the dialogue on cultural heritage management by proposing digital and institutional revitalization strategies to achieve sustainable educational tourism and to reinforce museums' role in fostering historical literacy and local identity formation.